Endoscopic lateral neck dissection via the breast and transoral approaches for papillary thyroid carcinoma: A preliminary report - Kuang, Penghao; Wang, Yuanyuan; Wu, Guoyang; Luo, Yezhe; Fu, Jinbo; Yan, Wei; Lin, Suqiong; Hong, Xiaoquan; Lin, Fusheng; Lin, Ende; Fu, Yilong (Frontiers in Surgery, 2022)
Purpose: Complete lymph node dissection is essential for the management of papillary thyroid carcinoma (PTC) with lymph node metastasis (LNM). This work aimed to describe the feasibility of endoscopic lateral neck dissection via the breast and transoral approach (ELNDBTOA) in PTC patients and the necessity of the addition of the transoral approach. Methods: We included 13 patients with PTC and suspected lateral LNM who underwent ELNDBTOA at the Zhongshan Hospital, Xiamen University. Total thyroidectomy, ipsilateral central lymph node dissection, and selective neck dissection (levels IIA, IIB, III, and IV) were performed endoscopically via the breast approach. Residual lymph nodes were further dissected via the transoral approach. Results: The mean operation time was 362.1 ± 73.5 min. In the lateral neck compartments, the mean number of retrieved lymph nodes was 36.6 ± 23.8, and the mean number of positive lymph nodes was 6.8 ± 4.7. Lymph nodes in the lateral neck compartment were obtained in nine patients (9/13, 69.2%), and three patients (3/13, 23.1%) had confirmed lateral neck metastases by further dissection via the transoral approach. Transient hypocalcemia occurred in two patients (2/13, 15.4%), and three patients (3/13, 23.1%) developed transient skin numbness in the mandibular area. No other major complications were observed. There was no evidence of local recurrence or distant metastasis during the follow-up period (range, 24-87 months). All patients were satisfied with the good cosmetic outcome. Conclusion: ELNDBTOA is an option with proven feasibility for select PTC patients with LNM, and the addition of the transoral approach is necessary to ensure complete dissection.